Edith Wharton and the modern privileges of age - Dawson, Melanie, 1967- (University Press of Florida, 2020)
"Focusing on the works of Edith Wharton and her contemporaries, Melanie Dawson discusses representations of modern American identities past early youth in twentieth-century literature. Dawson sets Wharton's work at the center of a vital debate about the contested privileges associated with age in contemporary culture"--